SOCIAL FOUNDATIONS OF STUDENTS’ MORAL DEVELOPMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Spiritual and moral education represents one of the fundamental processes in the formation of an individual as a socially responsible, ethically conscious, and culturally aware member of society. In modern conditions, this process is becoming increasingly complex due to the influence of globalization, digitalization, and the expansion of the information space. Therefore, it is essential to analyze the key factors that shape students’ moral development in a comprehensive and systematic way.